2013
DOI: 10.54652/rsf.2013.v43.i2.111
|View full text |Cite
|
Sign up to set email alerts
|

Antiphytoviral Effects of Three Different Essential Oils on Tobacco Mosaic Virus

Abstract: UDK 665.52:635.7]:632.38           632.38:633.71 Numerous studies have found that essential oils have significant inhibitory activity against human viruses, but there is scarce information on the effects of essential oils on plant viruses. In this study, effects of cajuput (Melaleuca leucadendron (L.) L.), common myrtus (Myrtus communis L.) and winter savory (Satureja montana L.) essential oils were assayed against Tobacco mosaic virus (TMV) by inoculation in different plant host systems. Antiphyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The experiments carried out in the present study confirmed that the following EOs extracted from different plants had antiphytoviral activity against the following viruses: Foeniculum vulgare EO and Pimpinella anisum EO—against Potato virus X (PVX) [ 9 ]; Plectranthus tenuiflorus EO—against Tobacco necrosis virus (TNV); Tomato spotted wilt virus (TSWV) and Tobacco mosaic virus (TMV) [ 10 ], Foeniculum vulgare EO, and Pimpinella anisum EO—against TMV and Tobacco ringspot virus (TRSV); Picrasma quassioides EO, Melaleuca leucadendron EO, Myrtus communis EO, and Satureja montana EO—against TMV [ 11 , 13 , 14 ]; Azadirachta indica EO, Clerodendrum inerme EO, Schinus terebinthifolius EO, and Mirabilis jalapa EO—against Bean common mosaic (BCMV) [ 15 ]; Tanacetum vulgare EO—against Potato virus Y (PVY) from [ 16 ]; Lavandula angustifolia EO and Foeniculum officinale All. var.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments carried out in the present study confirmed that the following EOs extracted from different plants had antiphytoviral activity against the following viruses: Foeniculum vulgare EO and Pimpinella anisum EO—against Potato virus X (PVX) [ 9 ]; Plectranthus tenuiflorus EO—against Tobacco necrosis virus (TNV); Tomato spotted wilt virus (TSWV) and Tobacco mosaic virus (TMV) [ 10 ], Foeniculum vulgare EO, and Pimpinella anisum EO—against TMV and Tobacco ringspot virus (TRSV); Picrasma quassioides EO, Melaleuca leucadendron EO, Myrtus communis EO, and Satureja montana EO—against TMV [ 11 , 13 , 14 ]; Azadirachta indica EO, Clerodendrum inerme EO, Schinus terebinthifolius EO, and Mirabilis jalapa EO—against Bean common mosaic (BCMV) [ 15 ]; Tanacetum vulgare EO—against Potato virus Y (PVY) from [ 16 ]; Lavandula angustifolia EO and Foeniculum officinale All. var.…”
Section: Discussionmentioning
confidence: 99%
“…Although limited, current knowledge about the antiviral effects of EOs indicates their potential to control the spread of viral infections [ 6 , 8 ]. A number of recent reports have provided data on the activity of EOs against plant viruses [ 4 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. However, this field of study is still insufficiently explored and further research is required to enable a more complete understanding of the mechanisms behind the antiviral activities of EOs [ 1 ].…”
Section: Introductionmentioning
confidence: 99%